Evolution of Bureaucratic Reform: A Comparative Analysis of Institutional Frameworks and Digital Governance in Indonesian and Malaysian State Administrations - Fitriana Fitriana; R.F.S Harapan Tua (Utan Kayu Publishing, 2025)
This article examines how institutional trajectories, merit-based civil service reforms, and digital governance interact to shape bureaucratic reform in two post-colonial states: Indonesia and Malaysia. The study addresses two questions: (1) how do differences in institutional frameworks and reform trajectories influence the design and implementation of merit-based administrative systems in both countries; and (2) to what extent do digital governance strategies reinforce or compromise meritocratic principles, transparency, efficiency, and citizen participation. Using a qualitative, literature-based comparative approach and a structured, focused comparison along three analytical dimensions (institutional trajectories, merit systems, and digital governance), the article synthesizes findings from academic studies, policy documents, and international indices. The analysis shows that Indonesia, moving from a highly centralized colonial and authoritarian legacy to radical decentralization, has developed a formally advanced merit framework but faces a persistent gap between rules and practice, producing a pattern of (strong formalization, weak enforcement). Malaysia, with a relatively stable federal, Westminster legacy, exhibits a (structured merit) system embedded in an ethnically based political settlement. In digital governance, Indonesia pursues ambitious but fragmented multi-level reforms, while Malaysia follows a more centralized and programmatic trajectory. The article concludes that global scripts of meritocracy and digital governance are refracted through historically specific institutional and political configurations.